High expression of partitioning defective 3–like protein is associated with malignancy in colorectal cancer. Issue 4 (April 2017) - Li, Taiyuan; Liu, Xiaoyang; Jiang, Qunguang; Lei, Xiong; Liu, Dongning
Partitioning defective 3–like protein is a novel cell polarity protein. Recently, partitioning defective 3–like protein has been demonstrated with tumor-promoting function by disrupting tight junction, inhibiting tumor suppressor liver kinase B1, and maintaining mammary stem cells. For the first time, we studied partitioning defective 3–like protein expression in malignant colorectal cancer. We used immunohistochemistry scoring system to evaluate partitioning defective 3–like protein expression in 196 colorectal cancer tissues and 33 adjacent normal tissues. We found that colorectal cancer tissues had much stronger partitioning defective 3–like protein immunoreactivity than normal tissues, and colorectal cancer patients with positive partitioning defective 3–like protein expression were characterized with higher cancer stages, metastasis, poor tumor differentiation, larger tumor size, as well as high levels of colorectal cancer markers carcinoembryonic antigen and cancer antigen 19-9. Besides, partitioning defective 3–like protein overexpression was independently predictive of lower survival rate in colorectal cancer patients, even after adjusting the influence of cofactors. Moreover, we also found that partitioning defective 3–like protein was associated with rapid growing colorectal cancer, while knockdown of partitioning defective 3–like protein expression largely inhibited cancer cell proliferation. Our study provided the first evidence that partitioning defective 3–like protein was overexpressed in colorectal cancer and associated with disease malignancy. Also, partitioning defective 3–like protein may serve as a promising prognostic marker and a potential therapeutic target for colorectal cancer treatment. Further study is necessary to understand the regulatory mechanism of partitioning defective 3–like protein in colorectal cancer and the feasibility of its application in clinic.